2021
DOI: 10.1002/mnfr.202100315
|View full text |Cite
|
Sign up to set email alerts
|

Oral Spermidine Targets Brown Fat and Skeletal Muscle to Mitigate Diet‐Induced Obesity and Metabolic Disorders

Abstract: Introduction Obesity causes many life‐threatening diseases. It is important to develop effective approaches for obesity treatment. Oral supplementation with spermidine retards age‐related processes, but its influences on obesity and various metabolic tissues remain largely unknow. This study aims to investigate the effects of oral spermidine on brown adipose tissue (BAT) and skeletal muscle as well as its roles in counteracting obesity and metabolic disorders. Methods and Results Spermidine is orally administr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 65 publications
(62 reference statements)
0
6
0
Order By: Relevance
“…Spermidine, as a natural polyamine that can be obtained from specific foods, has been found to play a key role in cell proliferation and is essential for the growth and development of children. Previous studies have suggested that spermidine supplementation may lead to varying degrees of improvement in weight status in high-fat diet-induced obese mice [17,18,20]. Moreover, an epidemiological study showed that spermidine intake was negatively associated with obesity [17].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Spermidine, as a natural polyamine that can be obtained from specific foods, has been found to play a key role in cell proliferation and is essential for the growth and development of children. Previous studies have suggested that spermidine supplementation may lead to varying degrees of improvement in weight status in high-fat diet-induced obese mice [17,18,20]. Moreover, an epidemiological study showed that spermidine intake was negatively associated with obesity [17].…”
Section: Discussionmentioning
confidence: 99%
“…Previous animal studies suggest that spermidine supplementation can help reduce body weight and improve metabolic disorders associated with obesity. In 2018, two animal studies consistently showed that spermidine supplementation caused a significant loss of weight and improved insulin resistance in high-fat diet-induced obese mice [17,18]. Furthermore, spermidine also can reduce the blood lipid level in high-fat diet-induced obese mice or acute hyperlipidemia mice [19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%
“…The study by Satish et al showed that mice with spermine treatment at a dose of 10 mg/kg resulted in a 24% reduction in body weight and an 18% reduction in fasting glucose [ 33 ]. Furthermore, as the decomposition product of spermine, spermidine has been well-known to be negatively correlated with lipid accumulation [ 37 , 38 ]. There are two pathways that convert spermine to spermidine ( Figure 6 B,C), including spermine oxidase which converts spermine into spermidine and 3-aminopropanal and acetylpolyamine oxidase, which converts spermine into spermidine and N-acetyl-1-spermine [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…While changes in circulating putrescine in NAFLD/NASH have not been reported yet and the evidence for decreased spermidine is limited ( 236 ), a number of studies reported a protective role of spermidine in mouse models of NAFLD. In diet-induced obese mice, supplementation with spermidine lowered hepatic steatosis associated with downregulation of lipogenic genes and upregulation of genes driving FAO, including Ppara ( 233 , 238 ). Also, spermidine ameliorated obesity-associated NAFLD in mice by increasing the phosphorylation of hepatic AMP-activated protein kinase (AMPK), which in turn inhibited the expression of the lipogenic genes Srebf1c and Fas ( 239 ).…”
Section: Emerging Biomarkers Linking Nafld/nash and Ascvd Offer Poten...mentioning
confidence: 99%